LIFESTYLE AND BRAND ASSOCIATION ON IPHONE SMARTPHONE PURCHASE DECISIONS IN AMBON - Victor Huwae; Erlinda Tehuayo; Etvin R Tamher; Fikri H M. Rumuar (Jurnal Ekonomi, 2023)
The purpose of this study aims to determine and analyze the effect of lifestyle and brand associations on purchasing decisions at Di.The type of research used was quantitative research, namely research that went directly to the field using a questionnaire as a data collection tool which was distributed to 103 respondents, Iphone smartphone consumers in the city of Ambon. This study used a sampling technique called purposive sampling. The results of the research that has been done, with multiple and partial linear regression analysis which shows that the influenceLifestyle and Brand Association have a positive and significant effect on Purchasing Decisions